MODERN APPROACHES TO THE DIAGNOSIS AND TREATMENT OF NONISCHEMIC (ARTERIAL) PRIAPISM - S. K. Yarovoi; R. A. Khromov; O. V. Dzhalilov (Исследования и практика в медицине)
The article analyzes information on prevalence, etiology, peculiarities of differential diagnosis, as well as indications and methods of surgical treatment of non-ischemic (arterial) priapism. The literature data are supplemented by the results of our own observations.The disease is characterized by a rarity and significant differences in therapeutic tactics in comparison with ischemic (venous) priapism. Arterial priapism occurs about 50 times less often than venous and in most cases is secondary to trauma of the penis, perineum or congenital abnormalities of the vessels of the penis. Primary, that is, unclear etiology, arterial priapism is described as a casuistic rarity.Laboratory-confirmed arterial priapism is a planned situation, not requiring immediate measures to stop the pathological erection, while the outcome of venous priapism directly depends on the duration of the disease and the success of emergency urological care.The main method of differential diagnosis of hemodynamic forms of priapism is the gasometry of blood obtained by puncture of cavernous bodies. The absence of hypoxia is a pathognomonic symptom of arterial priapism and serves as a rationale for angiography, the task of which is the topical diagnosis of vascular disorders.The revealed pathological vascular joints undergo superselective embolization. The effectiveness of the technique in terms of stopping the pathological erection is close to 100%.Surgical tactics do not depend on the etiology of arterial priapism: posttraumatic and “non-traumatic” variants of the disease imply an absolutely identical approach.Expectant  tactics  regarding  arterial  priapism  are  the  subject  of  scientific  discussion.  Despite  the  possibility  of an independent cessation of pathological erection with arterial priapism, due to the risk of developing cavernous fibrosis, expectant management is appropriate only in children with undisputed posttraumatic etiology of the disease. The observation period should not exceed 3–4 weeks.The prognosis of arterial priapism is much better than venous. Arterial priapism, as well as endovascular methods of its treatment are not accompanied by the risk of acute cavernitis. Erectile function, provided the timeliness of the intervention is preserved in virtually all patients.